Does eliminating the Form 20-F reconciliation from IFRS to U.S. GAAP have capital market consequences? - Kim, Yongtae; Li, Haidan; Li, Siqi (Journal of Accounting and Economics, 2012)
This paper investigates the capital market consequences of the SEC's decision to eliminate the reconciliation requirement for cross-listed companies following International Financial Reporting Standards (IFRS). We find no evidence that the elimination has a negative impact on firms' market liquidity or probability of informed trading (PIN). We also find no evidence of a significant impact on cost of equity, analyst forecasts, institutional ownership, stock price efficiency and synchronicity. Moreover, IFRS users do not increase disclosure frequency nor supply the reconciliation voluntarily. Our results do not support the argument that eliminating the reconciliation results in information loss or greater information asymmetry.